Implementation Of Sequential Searching Algorithm In Car Sales E-Commerce Web - Yuza Reswan; Yulia Darnita; A.R. Walad Mahfuzhi Mahfuzhi; Elviani Elviani (Penerbit Jurnal Indonesia, 2024)
The sequential searching algorithm is an algorithm that performs a search by matching the data to be searched with all the data in a group of data in a sequential manner starting from the first data until the data can be found. The development of information and communication technology has brought significant changes in various aspects of life, including in the world of commerce. E-commerce has become a popular platform for carrying out buying and selling transactions, including car sales. Selling cars via e-commerce offers many benefits for buyers and sellers. For buyers, e-commerce provides easy access to a wide selection of cars at competitive prices. For sellers, e-commerce expands their market reach and allows them to reach more customers. However, as the number of products available on e-commerce websites increases, finding the desired product becomes increasingly difficult. This can cause frustration for buyers and result in decreased sales. This research aims to discuss the implementation of sequential search algorithms on car sales e-commerce websites. This algorithm is expected to help buyers find the car they want more easily and quickly, thereby increasing buyer satisfaction and increasing sales for sellers.